Relationship between oral reading fluency and reading comprehension among ESL students - Khor, Ching Pey; Low, Hui Min; Lee, Lay Wah (Penerbit UKM, 2014)
Fluency is one of the five components of reading competency alongside with phonemic awareness, phonics, vocabulary and comprehension. It is related to reading comprehension and it can be used to predict the reading competency of a reader. However, research on such relationship is limited in ESL context. Hence, the purpose of this study was to determine the relationship between three sub-skills of fluency (accuracy, reading rate and prosody) and reading comprehension among a sample of ESL students in a Malaysian school. It also aims to examine the concurrent validity of using the objective (i.e. reading accuracy and rate) and subjective (reading prosody) measures of fluency. It is hoped that the findings could shed light in identifying the possible methods of assessing oral reading fluency in ESL classrooms. The participants were 67 lower secondary school students who learn English as their second language. The students completed a reading comprehension test and then they were asked to read aloud the texts used in the test, individually. The individual reading sessions were audio recorded for the analysis of three sub-skills of reading fluency. Bivariate correlation analysis was then conducted to measure the strength of relationships with reading comprehension. The results revealed that all three sub-skills of fluency were strongly correlated with reading comprehension. Both objective (accuracy and reading rate) and subjective (prosody) rating scales were strongly related, and thus could be used in parallel or interchangeably in the assessment of oral reading fluency. The findings provided evidence that in line with the research findings in English as the first language contexts, reading fluency is closely associated with reading comprehension in an ESL context.